Joint Activity in the Maritime Traffic System: Perceptions of Ship Masters, Maritime Pilots, Tug Masters, and Vessel Traffic Service Operators. (13th December 2016) - Mansson, Joakim Trygg; Lutzhoft, Margareta; Brooks, Ben
Abstract : Teamwork in the maritime traffic system has been identified as an area of concern, and reports suggest there is room for improvement. Such improvements should be based on an understanding of how everyday activities are performed. This study was therefore aimed at gaining an insight into the everyday activity of navigating and manoeuvring ships in port waters. To get such an insight, the perceptions of ship masters, maritime pilots, tug masters and Vessel Traffic Service operators active in Australia were probed through qualitative research interviews. A conceptual framework based on Clark's work on joint activity was used to guide the study. Results indicate that in order to get the job done, these maritime professionals employ tools and procedures beyond those intended to be used, vary their level of participation, assume roles which differ from those prescribed, sometimes base their assumptions and expectations on poor quality evidence, and occasionally avoid communication. While such adaptations may be necessary to get the job done, they also reduce the participants' ability to establish common ground – which is essential for coordination.